P–370 RPL-protease A as a potential biomarker for predicting recurrent pregnancy loss. (6th August 2021) - Pei, C Z; Park, H B; Choi, H S; Choi, B; Park, H Y; Jung, H Y; Baek, K H
Abstract: Study question: Could the reduction of RPL-protease A be involved in the dysfunctional trophoblast for resulting in recurrent pregnancy loss (RPL). Summary answer: Low expression of RPL-protease A may result in RPL and low serum RPL-protease A level may be a potential biomarker for predicting RPL. What is known already: The RPL-protease A is expressed and secreted by placenta. The RPL-protease A is involved in the pathogenesis of pre-eclampsia, and the serum RPL-protease A level is higher in the patients with pre-eclampsia than that of normal groups. In our previous study, we identified that the RPL-protease A mRNA level was lower in the villi of patients with RPL than that of normal groups. Study design, size, duration: Using the CRISPR/Cas9 system, the RPL-protease A gene knockout BeWo cell (BeWo KO) line was established, and the wild type (BeWo WT) and BeWo KO cells were applied to investigate the roles of RPL-protease A in trophoblasts. The human serum RPL-protease A levels were investigated by Western blot analysis and ELISA kit. Participants/materials, setting, methods: The cell-cell fusion, cell counting analysis, invasion and scratch wound assays, cell cycle analysis, and immunocytochemical analysis were used to investigate cellular functions of RPL-protease A in trophoblast. The sera were obtained from 32 normal pregnant women and 60 women with RPL. The Western blot analysis and ELISA were used for detection of serum RPL-protease A levels. Main results and the role of chance: The β-hCG was detected in fused BeWo WT cells, while the BeWo KO cells cannot fuse and did not express the β-hCG. The ability of invasion was decreased, but the capacity of migration and proliferation was higher in BeWo KO cells than BeWo WT cells. Cell fusion related factor (β-hCG), and cell invasion related factors (MMP–2 and MMP–9) were highly expressed in BeWo WT cells, and cell related factor (FAK), and cell proliferation related factors (ERK, p38, JNK, MKK3, MKK6, Raf, and Ras) were highly expressed in BeWo KO cells. The Western blot analysis and ELISA indicate that the serum RPL-protease A level was decreased in patients with RPL compared to that of normal groups. Limitations, reasons for caution: The results of this study have the limitation of RPL-protease A functions in vitro. Wider implications of the findings: The cellular functions of RPL-protease A in trophoblasts were investigated to explain the pathogenesis of RPL, and low serum RPL-protease A level can be used for a potential biomarker predicting RPL. Trial registration number: Not applicable